АТАҚ ҲӘМ ЛАЎАЗЫМ АТЛАРЫНАН ПАЙДА БОЛҒАН ТОПОНИМЛЕР - Абишов, Г.М. (SCIENCE and SOCIETY, 2016)
Toponyms mean the peculiarities of geographical objects and their names. There are different circumstances in the formation of toponyms. Toponyms of Chimbay region has their semantics. There have been analyzed the names of titles and professions and also the motives of origin and reasons of toponyms.
Keywords: title; appointment; hodja; ishan; ahun; hadji; minister; toponym